COGNITIVE UNDERPINNING OF POST TRAUMATIC STRESS DISORDER AMONG AFGHAN AND KYRGYZ STUDENTS: AN EMPIRICAL INVESTIGATION - Azizuddin Khan; Elena Molchanova; Zarlasht Sarmast; Farangis Dehnavi; Eshquvvatov To‘lqinjon Eshquvvatovich; Umrah Beg (The Indonesian Journal of Public Health, 2026)
Introduction: Post-traumatic stress disorder (PTSD) is a mental health condition precipitated by exposure to trauma, which manifests as enduring psychological distress. The prevalence of PTSD is around 42.2% among Afghans citizen (Kovess-Masfety et al., 2021).  Understanding the cognitive implications of PTSD is crucial for comprehending its impact on individuals' day-to-day functioning. Aim: This study explores the the cognitive mechanisms underlying post-traumatic stress disorder. Methods: The study employed 262 participants, investigating the effect of PTSD symptom severity on prospective memory (PM). Participants were categorized based on citizenship and PTSD symptom severity, resulting in two groups: 97 with low PTSD symptoms and 165 with high symptoms. These results underscore the intricate relationship between war-related traumas, citizenship status, and cognitive functioning. According to the study, Afghan students exposed to war conditions showed cognitive decline associated with PTSD. Results: The study results indicated that Afghan students have poorer PM performance, and the discrepancy is magnified when PTSD symptoms are taken into account. In particular, the performance gap was more evident among Afghan students experiencing high levels of PTSD symptoms compared to those with low symptom levels. Significant main effects of memory and citizenship indicated diverse cognitive responses across memory conditions and substantial performance score differences between citizenships. Main effects of PCLLH underscored symptom severity's influence on cognitive functioning, while the Citizenship-PCLLH interaction revealed a nuanced relationship not uniform across groups. Conclusions: The study enriches our understanding of cognitive outcomes in trauma-exposed populations, emphasizing the multifaceted interplay of memory, citizenship, and PTSD symptom severity.